Balancing the Stability–Activity Trade‐Off by Fine‐Tuning Dehalogenase Access Tunnels. Issue 4 (22nd January 2015) - Liskova, Veronika; Bednar, David; Prudnikova, Tatyana; Rezacova, Pavlina; Koudelakova, Tana; Sebestova, Eva; Smatanova, Ivana Kuta; Brezovsky, Jan; Chaloupkova, Radka; Damborsky, Jiri
Abstract A variant of the haloalkane dehalogenase DhaA with greatly enhanced stability and tolerance of organic solvents but reduced activity was created by mutating four residues in the access tunnel. To create a stabilised enzyme with superior catalytic activity, two of the four originally modified residues were randomised. The resulting mutant F 176 G exhibited 32‐ and 10‐times enhanced activity towards 1, 2‐dibromoethane in buffer and 40 % DMSO, respectively, upon retaining high stability. Structural and molecular dynamics analyses demonstrated that the new variant exhibited superior activity because the F 176 G mutation increased the radius of the tunnel's mouth and the mobility of α‐helices lining the tunnel. The new variant's tunnel was open in 48 % of trajectories, compared to 58 % for the wild‐type, but only 0.02 % for the original four‐point variant. Delicate balance between activity and stability of enzymes can be manipulated by fine‐tuning the diameter and dynamics of their access tunnels.